Formal Synthesis of Kanamienamide - Li, Yang; Guo, Yian; Xu, Zhengshuang; Ye, Tao (Synlett, 2018)
A formal total synthesis of the anticancer natural product kanamienamide has been accomplished. This communication describes two approaches to the macrocyclic core of the natural product. The key features of the route include an eﬃcient macrolactamization, a Corey–Bakshi–Shibata asymmetric reduction, and a Stork–Zhao–Wittig olefination.
Keywords: natural products; total synthesis; kanamienamide; macrocycles; lactams; lactones